Realizing studio project as part of the achievement of the Key Performance Indicators (KPI) for academics - Abdullah, Alias; Ahmad Sarkawi, Azila; Hj Mohd Ariffin, Noor Aziah (Infobase Creation Sdn Bhd, 2016)
Key Performance Indicators (KPI) is widely known as a measurement tool of work performance. In the International Islamic University Malaysia (IIUM), the six key performance indicators established for all academic staff are teaching, supervising, researching, consultancy, publication, and services to the public. However, academic staffs are struggling to strike a balance with all these indicators, as basis for their annual assessment. Academics in the built environment faculty particularly are of the opinion that their handling of studio projects was being underplayed despite 30% of their working time per week is in the studios. The studio project which is the integral and core component of the built environment education is merely recorded as teaching in the current KPI. This paper elucidated the workings of a studio project for the Department of Urban and Regional Planning (URP). The study contended that the elements involved in the completion of a Planning studio project have all the characteristics of the KPI and should be used as part of academics’ annual appraisal assessment. The paper utilised a content analysis of the course outlines and project briefs of six Planning studio projects and validated through an interview survey. Twelve academics of the Department of URP who handled the studio for academic session 2015/16 were the respondents. The study found that Planning studio projects embodied all the components of the KPI and its potential of applicability as academics’ KPI is high. The paper proposes two strategies. Firstly, a link needs to be established between the processes and outcomes of a studio project and that these be counted as part of an academic’s KPI. Secondly, is to formalise a method so that the outcomes of studio teaching are accepted as part of the achievement of the KPI.